Scottish Water: a public-sector success story. Issue 6 (18th September 2016) - Hendry, Sarah
ABSTRACT: This article explores the governance and regulation of water services in Scotland, including the emergence of a single national provider, Scottish Water; the role of government and its novel Hydro Nation strategy; and the activities of the regulators – for prices, environment, drinking water quality and consumer protection – as Scottish Water moved from amongst the lowest, to amongst the best, of its benchmarked comparators. It examines the recent initiative of a Customer Forum; and draws conclusions on the potential for a public service provider to evidence private-sector efficiency whilst contributing fully to public policy goals.